Optimizacija neprekinjenega postopka sušenja v težavnostnih sušilnicah - Voća, Neven (Strojniški vestnik, 2007)
Technology and technological expectations are expected to develop with time; however, opportunities, needs and working conditions affect the extent of their usage. Predictions are made in all areas of human activity, and this includes the agricultural sector. Using the know-how so far applied during thedrying process in gravity dryers, together with the available data on the interdependencies of a large number of parameters, this paper suggests how a system for drying could be organized by optimising the functional ensembles. Acomprehensive method for drying-process optimization in gravity dryers can be built in several steps from several functional ensembles. Each step improvesthe process, and together they represent the complete system for performance optimization. An additional property is the possibility of realizing each step. The drying-process optimization results in the stabilisation of the dryer functions, a decrease in the specific energy consumption, and better kernel quality.
Keywords: sušenje; sušilnice; optimiranje; učinkovitost; efficiency; krmiljenje